FAKTOR RISIKO RIWAYAT KONTAK, STATUS GIZI ANAK, DAN STATUS EKONOMI TERHADAP KEJADIAN TB ANAK DI KABUPATEN WONOSOBO - Faradina Pramesti Nandariesta; Lintang Dian Saraswati; Mateus Sakundarno Adi; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2019)
Tuberculosis (TB) children are an infectious disease caused by rod-shaped bacteria (bacilli) known as Mycobacterium tuberculosis and occur at the age of 0-14 years. Based on the Global Tuberculosis Report in 2017, as many as 500,000 children were affected by TB in 2016. The number of TB patients in Wonosobo District in 2017 was 1,442 cases, with the number of TB cases of children 337 cases. This study used an observational analytic research approach with a study design namely case control. The number of samples taken in this study were 96 respondents, with 48 cases and 48 controls. Analysis of the data used is the chi square test. The results of the chi-square analysis show that the variable which is the risk factor for the occurrence of Child TB in Wonosobo Regency is a history of contact with TB patients (OR = 5.8, p = 0.001). From these results it is expected that TB patients who live with children to use masks and also not throw phlegm carelessly to minimize transmission to children.